PENCEGAHAN PERILAKU HUSTLE CULTURE PADA KARYAWAN DI PT. PERTAMINA PATRA NIAGA REGIONAL SULAWESI MELALUI PSIKOEDUKASI NON-PELATIHAN - Irma, Irma; Azzahra, Raodahtun Qori; Patiung, Rita; Bakar, Resekiani Mas (LPPM Institut Pendidikan Nusantara Global, 2022)
Hustle culture is a culture that makes individuals adopt workaholism or workaholism behavior. Through the Professional Work Lecture program, Students of the Faculty of Psychology, Makassar State University carry out community service at PT. Pertamina Patra Niaga Regional Sulawesi. The purpose of this service is to prevent hustle culture behavior among employees. The method used is non-training psychoeducation with the help of banners and posters. The method used in data collection is a survey that is distributed via Google form and analyzed descriptively. Based on the survey conducted, it was found that the average employee is in the middle category who experiences the characteristics of hustle culture with a percentage of 72.3%. After employees are given psychoeducation there are 90% of employees at PT. Pertamina Patra Niaga Regional Sulawesi which is committed to reducing hustle culture behavior.